2021
DOI: 10.3390/genes12121925
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Shell Matrix Proteins of Nautilus pompilius and the Identification of a Core Set of Conchiferan Domains

Abstract: Despite being a member of the shelled mollusks (Conchiferans), most members of extant cephalopods have lost their external biomineralized shells, except for the basally diverging Nautilids. Here, we report the result of our study to identify major Shell Matrix Proteins and their domains in the Nautilid Nautilus pompilius, in order to gain a general insight into the evolution of Conchiferan Shell Matrix Proteins. In order to do so, we performed a multiomics study on the shell of N. pompilius, by conducting tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
(87 reference statements)
1
10
2
Order By: Relevance
“…Similar trends are also known from other mollusks, where unassigned and undescribed genes expressed in shell- and plate-forming cells appear to be highly taxon-specific. For example, secretomes from adult gastropods, bivalves, polyplacophorans, and a nautiloid cephalopod show considerable levels of lineage-specific orphan genes ( Jackson et al, 2006 , 2009 ; Immel et al, 2016 ; Kocot et al, 2016 ; Marin, 2020 ; Setiamarga et al, 2021 ). It has been argued previously that the rapid evolutionary rate of these genes may be a possible reason for the lack of orthology detection of these shell matrix toolbox genes ( Aguilera et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends are also known from other mollusks, where unassigned and undescribed genes expressed in shell- and plate-forming cells appear to be highly taxon-specific. For example, secretomes from adult gastropods, bivalves, polyplacophorans, and a nautiloid cephalopod show considerable levels of lineage-specific orphan genes ( Jackson et al, 2006 , 2009 ; Immel et al, 2016 ; Kocot et al, 2016 ; Marin, 2020 ; Setiamarga et al, 2021 ). It has been argued previously that the rapid evolutionary rate of these genes may be a possible reason for the lack of orthology detection of these shell matrix toolbox genes ( Aguilera et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, deciphering the molecular mechanisms that control shell secretion has received particular focus (Clark et al 2020). A range of gastropod (Herlitze et al 2018; Marie et al 2010), cephalopod (Marie et al 2009; Setiamarga et al 2020) and bivalve (Arivalagan et al 2017; Sleight et al 2016a) shells have been subject to proteomic sequencing, coupled to the transcriptomic investigation of the shell-secreting mantle tissue (Arivalagan et al 2016; Sleight et al 2016b), resulting in large lists of candidate shell-forming genes and proteins. Comparative methods have found that despite the “deep” homology of molluscan shells and shell plates (Vinther 2015), the molecular mechanisms that control biomineralisation in molluscs – particularly the downstream effectors such as the shell matrix proteins - are extraordinarily diverse (Jackson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, deciphering the molecular mechanisms that control shell secretion has received particular focus (Clark et al 2020). A range of gastropod (Herlitze et al 2018;Marie et al 2010), cephalopod (Marie et al 2009;Setiamarga et al 2020) and bivalve (Arivalagan et al 2017;Sleight et al 2016a) shells have been subject to proteomic sequencing, coupled to the transcriptomic investigation of the shell-secreting mantle tissue (Arivalagan et al 2016;Sleight et al 2016b), resulting in large lists of candidate shell-forming genes and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This volume is clearly not intended to be an exhaustive collection of studies on invertebrate animals, but we hope that the collection of articles presented here will give a general idea of both the type of studies carried out with invertebrate metazoans and the diversity of animal models used. Thus, we can read works carried out with Acropora corals [ 1 ], with several mollusc species such as the cephalopod Nautilus pompilius [ 2 ], the gastropod Crepidula fornicata [ 3 ] or the bivalve Mytilus galloprovincialis [ 4 ], as well as a study with the planarian Schmidtea mediterranea [ 5 ], or with several chordates such as two cephalochordate species ( Branchiostoma lanceolatum [ 6 ] and Branchiostoma floridae [ 7 ]) and two urochordate species ( Ciona robusta [ 8 ] and Phallusia mammillata [ 4 ]).…”
mentioning
confidence: 99%
“…In addition to the study of the evolution of gene families, access to high throughput data also allows the identification and study of genes involved in biological processes. Thus, the work presented by Setiamarga and collaborators [ 2 ] analyses the content of genes encoding shell matrix proteins in the mollusc Nautilus , an example of a cephalopod that has not lost its external biomineralized shell. The results demonstrate the presence of such genes in the ancestor of shelled mollusks (Conchiferans) but show that their function in shell formation was acquired during the evolution of this lineage independently in each clade.…”
mentioning
confidence: 99%